Long-term Electricity Power Forecasting at PT PLN UP3 Kediri Using Trend and Monte Carlo Simulation Methods - Naizatul Zainul Rofiqi; M. Cahyo Bagaskoro; Sujito; Langlang Gumilar; Aripriharta, Aripriharta (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
Community consumption power in the use of electricity resources is growing very rapidly. This is because the power source is the main need for the community. Without electricity, daily needs cannot run smoothly. In various regions, especially Kediri, where the needs are changing, it is necessary to predict and provide electricity to meet the consumption needs of the people. There are many things that can be done to predict the need for electric power, one of which is forecasting. Forecasting methods that can be used include trend and Monte Carlo Simulation. The results of this study indicate that Monte Carlo simulations are better at predicting long-term electrical power requirements at ULP3 Kediri. Long-term electricity demand can be predicted with the equation: Yt =138691 + 6709 x t + 231 x t2. The results of the research can help PLN UP3 Kediri to provide electricity for consumers.